Evaluation of the Physicochemical Properties of Vermicompost from Red Californian Worm (Eisenia foetida) and Bocashi (Agro Productividad, 2025)
The physicochemical properties of two types of organic fertilizers bocashi and vermicompost from red Californian worm (Eisenia foetida) were evaluated to determine their effectiveness as soil amendments. The study was conducted at the agroecological module of the Facultad Maya de Estudios Agropecuarios, Universidad Autónoma de Chiapas. The variables analyzed included pH, electrical conductivity, total organic carbon (TOC), total nitrogen (N total), carbon/nitrogen ratio (C/N), moisture content, and cation exchange capacity (CEC). Results showed that bocashi exhibited an alkaline pH (8.02), a high TOC content (13.85%), and total nitrogen (1.12%), demonstrating its strong potential to enhance soil fertility. Its water retention capacity and diverse nutrient profile make it particularly suitable for sustainable agriculture.The vermicompost from Eisenia foetida displayed a pH of 6.31 and a TOC of 10.79%, indicating its effectiveness in improving agricultural soils, especially for vegetable cultivation, although with slightly lower nutrient content than bocashi. Both organic fertilizers presented favorable physical properties, such as low bulk density and high porosity, which are essential for improving soil structure and water retention. Additionally, the cation exchange capacity of bocashi (37.47 cmol/kg) and vermicompost (33.21 cmol/kg) reflects a high nutrient retention capacity, beneficial for plant growth.